Chaperone-mediated autophagy prevents cellular transformation by regulating MYC proteasomal degradation. Issue 5 (4th May 2017) - Gomes, Luciana R.; Menck, Carlos F. M.; Cuervo, Ana Maria
ABSTRACT: Chaperone-mediated autophagy (CMA), a selective form of protein lysosomal degradation, is maximally activated in stress situations to ensure maintenance of cellular homeostasis. CMA activity decreases with age and in several human chronic disorders, but in contrast, in most cancer cells, CMA is upregulated and required for tumor growth. However, the role of CMA in malignant transformation remains unknown. In this study, we demonstrate that CMA inhibition in fibroblasts augments the efficiency of MYC/c-Myc-driven cellular transformation. CMA blockage contributes to the increase of total and nuclear MYC, leading to enhancement of cell proliferation and colony formation. Impaired CMA functionality accentuates tumorigenesis-related metabolic changes observed upon MYC-transformation. Although not a direct CMA substrate, we have found that CMA regulates cellular MYC levels by controlling its proteasomal degradation. CMA promotes MYC ubiquitination and degradation by regulating the degradation of C330027C09Rik/KIAA1524/CIP2A (referred to hereafter as CIP2A), responsible for MYC stabilization. Ubiquitination and proteasomal degradation of MYC requires dephosphorylation at Ser62, and CIP2A inhibits the phosphatase responsible for this dephosphorylation. Failure to degrade CIP2A upon CMA blockage leads to increased levels of phosphorylated MYC (Ser62) and to stabilization of this oncogene. We demonstrate that this phosphorylation is essential for the CMA-mediated effect, since specific mutation of this site (Ser62 to Ala62) is enough to normalize MYC levels in CMA-incompetent cells. Altogether these data demonstrate that CMA mitigates MYC oncogenic activity by promoting its proteasomal degradation and reveal a novel tumor suppressive role for CMA in nontumorigenic cells.